REALISASI ITS-90 UNTUK RENTANG 232 C – 962 OC PADA KE LP4 - Wiriadinata, Hidayat (Instrumentasi, 2013)
The realization of ITS-90 has been done using the monochromatic radiation thermometer KE LP4 80-59 over a temperature range 232C - 962 C and wavelength 1.57 µm. The method used is the method of Sakuma-Hattori using fixed-point black body calibrator tin, aluminum and silver. The value of uncertainty of the KE LP4 80-59 at the temperature range for 95% confidence level and a coverage factor of k = 2, is expressed by the equation: U(t) = 1,067461375 – 0,008000541.t + 2,586471.10-5.t2 -3,33928.10-8.t3 + 1,497270.10-12.t4 Keywords : the realization of ITS-90, the method of Sakuma-Hattori, the monochromatic radiation thermometer.